Guidelines for Monitoring the Implementation of Annual Action Plan of Primary Educational Service Area Office by Applying of Empowerment Evaluation - Bunbamrung, Teerawan; Tungprapa, Taviga; Naiyapatana, Ong-art (Interdisciplinary Academic and Research Journal, 2023)
Monitoring the implementation according to the annual action plan of the Primary Educational Service Area Office is an important process that helps increase the efficiency of operations to achieve specific operational goals. This research aims to 1) study the implementation according to the annual action plan of the Primary Educational Service Area Office with good performance, 2) develop guidelines for monitoring the implementation according to the annual action plan of the Primary Educational Service Area Office, applying the empowerment evaluation, and 3) check the quality of the developed guidelines. There are 3 phases in this research. Phase 1 is monitoring the implementation according to the annual action plan of the Primary Educational Service Area Office with good performance. Ten participants were interviewed in this phase. Phase 2 is the guideline development for monitoring the implementation according to the annual action plan. A focus group discussion with 9 experts was applied for this phase. Phase 3 is the quality check on the guidelines. Three hundred fifty-four participants were interviewed using interview forms, focus group discussions, and questionnaires. The data statistics were achieved using percentage, frequency distribution, mean standard deviation, and content analysis. The results show that 1) there are 5 monitoring principles, 4 groups of stakeholders, 4 main strategies and 23 sub-strategies of monitoring methods/strategies, 3 monitoring tools, and 17 evidence traces in operating check from monitoring the implementation according to the annual action plan of the Primary Educational Service Area Office with good performance. 2) There are 7 guidelines for monitoring the implementation according to the annual action plan of the Primary Educational Service Area Office applying the empowerment evaluation. They consist of 1) 3 sub-objectives of monitoring, 2) 5 monitoring principles, 3) the content framework of monitoring with 4 main issues and 22 subpoints, 4) 4 indicators of monitoring, 5) 4 groups of stakeholders, 6) 1 monitoring tool, and 7) 4-step monitoring process and 2 tactics. 3) The quality of guidelines for monitoring the implementation according to the annual action plan of the Primary Educational Service Area Office, applying the empowerment evaluation, shows utilization standards, feasibility standards, suitability standards, and accuracy standards at a high level in all aspects.